HUBUNGAN PENGETAHUAN IBU TENTANG GIZI ANAK USIA 0â5 TAHUN DENGAN STATUS GIZI ANAK (STUDI ANALITIK DI POSYANDU DUSUN SUKABUMI DESA SIMAN KECAMATAN KEPUNG TAHUN 2008) - Sukatmi, Sukatmi; Nugroho, Christianto; Agustina, Erni (Jurnal AKP, 2010)
Nutrition status ofchild represent situation of body as effect of consumption and usage ofnutritionAgechild of under five year represent factionwhich is to anger easily to problem of and health ofnutritionamongothers is problem less protein energyrepresenting the problem of especialnutritionin Indonesia. Intention ofthis research is to identify relation link knowledge of mother about age child nutrition0-5 year with status ofnutritionchild in Posyandu of Sukabumi Countryside of Siman District Besiege year 2008.The researchdesign iscorrelation study with population counted 37 and people of sample 34 responderwith data sampling consecutive, collected by giving questionnaireat mother and observation of heavy child.Afterwards dataanalyzedby using correlation test of spearman with value of significance0,05.From result of research got by most good enough knowledgeable mother bring in hand age child nutrition0-5 year that is equalto 58.8% and most status of childnutrition in level of good nutrition is55,9%. Fromresult of correlation test of spearman got by value of significance0,263 > 0,05 meaning H0 accepted. Thismatter explain that do not there are relation link among between knowledge of mother about age child nutrition0-5 year with status ofchild nutrition.Theknowledgeon the child nutrition arevital importance owned by mother, in order to can correctupbringing atits ducky especially in accomplishment of its requirement of him. But, knowledge had by mother isnot solely absolutefactor influence its child nutrition status. Because there is many other factor, like economicstatus of family, food sanitation, appetiteeat, amount and many other factor.